Multifaceted fish diversities respond differently to impounding age and longitudinal location along a reservoir cascade - Liao, Chuansong; Wang, Jiacheng; Ye, Shaowen; Li, Wei; Correa, Sandra Bibiana; Zhang, Tanglin; Liu, Jiashou (Frontiers in Ecology and Evolution, 2022)
Damming usually modifies riverine habitats, which affects various aspects of fish diversity, especially in a reservoir cascade. Their influence on fish assemblage has been studied widely, but a lack of data from the diversity perspective remains. The Gezhouba Reservoir and Three Gorges Reservoir are two of the largest cascaded reservoirs located on the upper Yangtze River. In this study, we investigated the current fish assemblages in 2020~2021 and retrieved 22 previous investigations in different sections of this cascade system to analyze how fish taxonomic, functional, and phylogenetic alpha- and beta-diversity changes with the distance from the dams and the impounding age during 1998~2021, and all sampling sites are located in the upper section of the dams. The total species richness and phylogenetic diversity increased with the distance from the dams significantly, but the functional diversity did not change substantially. No significant difference was found in the influence of impounding age on the three aspects of fish diversity. We observed a noticeable increase in non-indigenous fish species richness, functional diversity, and phylogenetic diversity over time, these effects were similar in areas at different distances from the dams. The species richness and phylogenetic diversity of lotic fish decreased from the lotic to lentic zones, whereas the functional and phylogenetic diversities decreased significantly with impounding age. The taxonomic beta-diversity was remarkably higher than the functional and phylogenetic beta-diversities. The differences among the three facets of beta-diversity were driven by a lower functional turnover than the taxonomic and phylogenetic turnovers, and their nestedness components were low without exception. The present study suggests that trade-off should be considered when designing policies to protect fish diversity based on different objectives.